POTENSI INFUSA BUNGA KEMBANG SEPATU (Hibiscus rosa-sinensis) SEBAGAI ANTI HIPERURISEMIA PADA MENCIT (Mus musculus) - Fatimatuzzahra Fatimatuzzahra; Dian Fita Lestari (Jurnal Biosilampari : Jurnal Biologi, 2022)
Uric acid levels in the blood can be lowered by taking anti-hyperuricemic drugs, but long-term use can have serious effects on the body. Therefore, we need medicines made from natural ingredients that have a compound that can reduce uric acid levels with a low effect. The purpose of this study was to determine the effect of hibiscus flower infusion on uric acid levels. The research method is experimental research with a Completely Randomized Design (CRD). Mice were divided into 6 treatment groups, the negative control group (normal) A0 was given 0.5% Na-CMC, A1 was hyperuricemia control (induction of potassium oxonate 250mg/kgBW and chicken liver juice), A2-A5 was treated with hyperuricemia. The treatment group A2 was given allopurinol 10mg/kgBW, A3-A5 was given hibiscus flower infusion at a dose of 20%, 30%, and 40%, respectively. The results showed that hibiscus flower infusion at doses of 20%, 30%, and 40% was able to reduce blood uric acid levels in male white mice induced by potassium oxonate and chicken liver juice. Hibiscus flower infusion has the potential to reduce uric acid levels in mice optimally at a dose of 20%, which is 80.8% of hyperuricemia control.